Lifespan diffusion MRI reveals regional abnormalities in the 5xFAD model of Alzheimer's disease: Neuroimaging / animal imaging. (7th December 2020) - Jullienne, Amandine; Lee, Jeong Bin; Yassa, Michael A.; Territo, Paul R; Obenaus, Andre; Consortium, MODEL‐AD
Abstract: Background: The Model Organism Development and Evaluation for Late‐Onset Alzheimer's Disease (MODEL‐AD) Consortium has been established to develop the next generation of Alzheimer's disease (AD) models based on human data. We undertook lifespan diffusion magnetic resonance imaging (dMRI) to fully characterize the temporal alterations in brain structure and circuits in 5xFAD. Method: All 5xFAD mice are compared to age‐matched littermates (C57BL/6J, WT) at 4, 8, and 12mo. Mice underwent high resolution diffusion tensor imaging (DTI) magnetic resonance imaging (MRI) at 9.4T (5 B0, 30 directions b=3000 mm 2 /sec) to assess regional white and gray matter. Regional tissue features were extracted from fractional anisotropy (FA), radial (RD), axial (AD) and mean (MD) diffusivity parametric maps. Tractography was performed based on the AMBMC mouse atlas. 18F‐AV45 PET was performed to quantitate amyloid β (Aβ) load. Histology and immunohistochemical analyses verified neuroimaging findings. Result: Our preliminary results focus on CA1 and the subiculum of the hippocampus and show tract differences between WT and 5xFAD females at 8 months of age. DTI metrics in these tracts are also affected by sex and genotype. For example, FA is decreased by ∼30% in 5xFAD females compared to WT females at 8 months. AV45‐PET were able to detect increasing Aβ plaque load with age in 8‐12mo old 5xFAD mice when compared to WT and was verified by immunohistochemistry. Conclusion: Phenotyping of mouse models using dMRI can identify altered brain connectivity and regional tissue features. The data support that increasing Aβ deposition results in altered dMRI metrics that can be readily translated to the clinic.